2017
DOI: 10.2147/oajsm.s127948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-paced active recovery and passive recovery on blood lactate removal following a 200 m freestyle swimming trial

Abstract: PurposeThe aim of this study was to investigate the effect of self-paced active recovery (AR) and passive recovery (PR) on blood lactate removal following a 200 m freestyle swimming trial.Patients and methodsFourteen young swimmers (with a training frequency of 6–8 sessions per week) performed two maximal 200 m freestyle trials followed by 15 minutes of different recovery methods, on separate days. Recovery was performed with 15 minutes of passive rest or 5 minutes of passive rest and 10 minutes of self-paced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
4
24
0
2
Order By: Relevance
“…During an intense aerobic exercise session, lactatemia increases abruptly ( 17 , 18 ), resulting in elevation of the lactate/pyruvate ratio (indicative of the redox state - NADH:NAD + ratio), as a consequence of the reduction of pyruvate to lactate through lactate dehydrogenase ( 19 ). In this condition, the brain could receive a considerable lactate supply.…”
Section: Discussionmentioning
confidence: 99%
“…During an intense aerobic exercise session, lactatemia increases abruptly ( 17 , 18 ), resulting in elevation of the lactate/pyruvate ratio (indicative of the redox state - NADH:NAD + ratio), as a consequence of the reduction of pyruvate to lactate through lactate dehydrogenase ( 19 ). In this condition, the brain could receive a considerable lactate supply.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the rate at which the lactate concentration is reduced in blood—and to a lesser extent, muscle tissue—has frequently been used as an objective indicator of recovery from exercise. A large body of research has shown that a variety of low- to moderate-intensity active cool-down protocols are more effective than a passive cool-down for removing lactate from blood [ 52 – 69 ] and muscle tissue [ 58 , 64 ]. However, there are some conflicting findings, with some studies reporting no significant difference—and sometimes even a slower removal of lactate in blood [ 44 , 70 ] or muscle [ 66 , 68 ]—as a result of an active cool-down.…”
Section: Physiological Effects Of An Active Cool-downmentioning
confidence: 99%
“…If more players have a bad physical condition during the match, it will decrease the team achievement as a whole (Abdulullah, 1981). Therefore, football player should also have a fast recovery process in which active recovery is one of the most effective recovery methods for increasing the speed of blood flow through the working muscle system (Mota, Elias, Oliveira-silva, Sales, & Sotero, 2017). Besides, active and combined recovery can reduce the level of fatigue in football athletes (Kurniawan, R., & Elfarabi, A, 2018).…”
Section: Discussionmentioning
confidence: 99%